Dosimetric impacts of endorectal balloon in CyberKnife stereotactic body radiation therapy (SBRT) for early‐stage prostate cancer. (13th April 2017) - Xiang, Hong F.; Lu, Hsiao‐Ming; Efstathiou, Jason A.; Zietman, Anthony L.; De Armas, Ricardo; Harris, Kathryn; Bloch, B. Nicolas; Qureshi, Muhammad Mustafa; Keohan, Sean; Hirsch, Ariel E.
Abstract: Purpose: In SBRT for prostate cancer, higher fractional dose to the rectum is a major toxicity concern due to using smaller PTV margin and hypofractionation. We investigate the dosimetric impact on rectum using endorectal balloon (ERB) in prostate SBRT. Materials and Methods: Twenty prostate cancer patients were included in a retrospective study, ten with ERB and 10 without ERB. Optimized SBRT plans were generated on CyberKnife MultiPlan for 5 × 7.25 Gy to PTV under RTOG‐0938 protocol for early‐stage prostate cancer. For the rectum and the anterior half rectum, mean dose and percentage of volumes receiving 50%, 80%, 90%, and 100% prescription dose were compared. Results: Using ERB, mean dose to the rectum was 62 cGy ( P = 0.001) lower per fraction, and 50 cGy ( P = 0.024) lower per fraction for the anterior half rectum. The average V50%, V80%, V90%, and V100% were lower by 9.9% ( P = 0.001), 5.3% ( P = 0.0002), 3.4% ( P = 0.0002), and 1.2% ( P = 0.005) for the rectum, and lower by 10.4% ( P = 0.009), 8.3% ( P = 0.0004), 5.4% ( P = 0.0003), and 2.1% ( P = 0.003) for the anterior half rectum. Conclusions: Significant reductions of dose to the rectum using ERB were observed. This may lead to improvement of the rectal toxicity profiles in prostate SBRT.